y-43/6=7

Simple and best practice solution for y-43/6=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-43/6=7 equation:



y-43/6=7
We move all terms to the left:
y-43/6-(7)=0
determiningTheFunctionDomain y-7-43/6=0
We multiply all the terms by the denominator
y*6-43-7*6=0
We add all the numbers together, and all the variables
y*6-85=0
Wy multiply elements
6y-85=0
We move all terms containing y to the left, all other terms to the right
6y=85
y=85/6
y=14+1/6

See similar equations:

| 3t=1.5t+24 | | 8^2x+6=8^4x-8 | | 7n+14-3n=4n-12 | | (4x)(5x+8)=0 | | 4x+10=6x=22 | | h-48/5=6 | | n+(n+1)+(n+2)+(n+3)=196 | | 17=1-4b | | 2c–4=5c-13 | | 6^8(x)=1296 | | 6a-7=5a-7a-15 | | -4+p/4=-3 | | -3(x-13.3)=-16.8 | | -15+3x-17x=-43 | | -12x-3x=36 | | m-91/2=3 | | -2-4p=5-5p | | 484=22f | | 10^(x)=10000 | | 5c+3–2c–4=3c–1 | | 2/3x-2=6+11/12x | | 1/3x=45* | | 5h-5=25 | | 39=6h-9 | | -15+3x17x=-43 | | 65,000=10,000(1.06)3x | | 10+7w=5w-10 | | 10−a=8 | | v+13/5=8 | | 14=5u-6 | | 96=20+4x4 | | 56.52=(3.14r)2 |

Equations solver categories